The Influence of Green Marketing Tools on Green Eating Efficacy and Green Eating Behaviour - Muposhi, A; Dhurup, M (Journal of Economics and Behavioral Studies, 2017)
This study employs the Legitimacy Theory and Self-efficacy Theory to examine the potential role of green marketing tools in fostering green eating behaviour. Using the mall-intercept technique at major retailers, data were collected using a self-administered questionnaire survey on South African consumers who regularly buy green products. Data analysis was conducted with the aid of the Statistical Package for the Social Sciences (SPSS) 22.0.The results indicate that South African consumers are significantly influenced by eco-labels and eco-brands when buying green products. The study, however, shows a negative relationship between green advertising and green eating efficacy. It also reveals a positive relationship between green eating efficacy and green eating behaviour. The findings of the study highlighted important implications and policy directions that marketers and policy makers may implement in order to promote green eating behaviour.